Dimensional analysis of Ni‐NiO grains at anode/electrolyte interface for SOFC during redox reaction. Issue 4 (15th March 2017) - Liang, Bo; Zhang, Silong; Zhang, Zefang; Lu, Biao; Lu, Shengguo; Kendall, Michaela; Ni, Meng
Abstract: Upon reduction and re‐oxidization, the interface of a microtubular solid oxide fuel cell (MTSOFC) anode/electrolyte was structurally analyzed using a dual beam focused ion beam/scanning electron microscope (FIB/SEM) and scanning transmission electron microscopy combined with energy dispersive X‐ray spectrometer (STEM‐EDX). The bulk volume of the dense NiO phase dramatically contracted upon reduction, while the YSZ phases are completely unaffected. No cracks or particle detachment are observed either at the interface of the anode/electrolyte or in the anode backbone. Compared with the initial NiO state (as‐prepared), the area of Ni phase contracts by 22.6%‐83.7%, depending on the grain size.